Efficient gene targeting of the Rosa26 locus in mouse zygotes using TALE nucleases - Kasparek, Petr; Krausova, Michaela; Haneckova, Radka; Kriz, Vitezslav; Zbodakova, Olga; Korinek, Vladimir; Sedlacek, Radislav (FEBS letters, 2014)
Gene targeting in mice mainly employs homologous recombination (HR) in embryonic stem (ES) cells. Although it is a standard way for production of genetically modified mice, the procedure is laborious and time-consuming. This study describes targeting of the mouse Rosa26 locus by transcription activator-like effector nucleases (TALENs). We employed TALEN-assisted HR in zygotes to introduce constructs encoding TurboRFP and TagBFP fluorescent proteins into the first intron of the Rosa26 gene, and in this way generated two transgenic mice. We also demonstrated that these Rosa26-specific TALENs exhibit high targeting efficiency superior to that of zinc-finger nucleases (ZFNs) specific for the same targeting sequence. Moreover, we devised a reporter assay to assess TALENs activity and specificity to improve the quality of TALEN-assisted targeting.
Keywords: Genetic Loci; sekvence nukleotidů; genetické lokusy; Endonucleases; Homologous recombination; Transcription activator-like effector nucleases; zygota; Homologous Recombination; Rosa26 locus; Gene targeting; genový targeting; Transgenic; Gene Targeting; homologní rekombinace; endonukleasy; Animals; myši transgenní; zvířata; myši; Base Sequence; Zygote; Mice; Mice, Transgenic; Zinc-finger nucleases